2018
DOI: 10.1111/febs.14615
|View full text |Cite
|
Sign up to set email alerts
|

The chromatin remodeling protein INO80 contributes to the removal of H2A.Z at the p53‐binding site of the p21 gene in response to doxorubicin

Abstract: Transcriptional activation of p21 (cyclin-dependent kinase inhibitor 1A) due to DNA damage often alters the distribution of histone variant H2A.Z at the p21 gene. However, whether the human INO80 complex regulates changes in H2A.Z at the p21 promoter is unclear. We show here that activation of p21 expression by doxorubicin (Doxo) in U2OS cells is required for removal of H2A.Z by INO80 at the p53-binding site proximal region (-2.2 kb) of the p21 promoter. A purified INO80 complex, but not the INO80E653Q mutant-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…10B ), the latter explained by its role of histone acetylation in recruitment of DNA repair machinery to dsDNA break sites [52]. The Ino80 complex influences doxorubicin response in fission yeast [141, 142], further suggesting evolutionary conservation of this interaction, and thus potential relevance to mammalian systems [143]. DNA repair pathways, such as those involving RAD52 and INO80 , are evolutionarily conserved, involved in genome instability and tumorigenesis [144], and predictive of therapeutic response in some cancers [145], thus representing potential tumor-specific biomarkers for chemotherapeutic efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…10B ), the latter explained by its role of histone acetylation in recruitment of DNA repair machinery to dsDNA break sites [52]. The Ino80 complex influences doxorubicin response in fission yeast [141, 142], further suggesting evolutionary conservation of this interaction, and thus potential relevance to mammalian systems [143]. DNA repair pathways, such as those involving RAD52 and INO80 , are evolutionarily conserved, involved in genome instability and tumorigenesis [144], and predictive of therapeutic response in some cancers [145], thus representing potential tumor-specific biomarkers for chemotherapeutic efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies by several authors (Ding, 2018;Sui, 2019;Meliala, 2020; showed that the transactivation of p21 (cyclin-dependent kinase inhibitor 1A) is closely related to the recruitment of transcription cofactors at the p53 responsive elements (p53REs) in its promoter region. Human chromatin remodeling enzyme INO80 can be recruited to the p53REs of the p21 promoter and negatively regulates p21 (Ding, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Our data, combined with previously reported data, have confirmed that YY1 can be recruited at the p53 binding site in the p21 promoter and be involved in the regulation of p21 transcription [9,13], suggesting that the recruitment of INO80 complex to the p53 binding site of the p21 TSS may be achieved by YY1. Based on the most recent report, the recruitment of INO80 complex to the p53 binding site in the p21 promoter may function in two different ways according to the intracellular condition: i) the INO80 complex represses p21 expression by regulating the promoter proximal nucleosome arrangement under normal cellular conditions; ii) in Doxo-treated cells, the INO80 complex rapidly removes accumulated H2A.Z and relieves its inhibition of p21 , thereby inducing the transcriptional expression of p21 [27].…”
Section: Discussionmentioning
confidence: 99%